Food Traceability in Supply Chain Based on EPCIS Standard and RFID Technology - Evizal Abdul Kadir; Siti Mariyam Shamsuddin; Eko Supriyanto; Wahyudi Sutopo; Sri Listia Rosa (Institute of Advanced Engineering and Science, 2015)
The growth of retailer lately very significant especially in food product, selling of food product is not only in conventional market but moreover now is in such mini market, mall, shopping complex, etc. Food traceability is required in supply of food product to make sure items are safe to consume and not in expired date. This paper present on food traceability in supply chain based on Electronic Product Code Information Services (EPCIS), the use of EPCIS standard is refer to Global Standard-1 (GS1) for logistic and supply chain based on Radio Frequency Identification (RFID) Technology. RFID is used for items tagging on food product instead of barcode that currently widely used the advantages of RFID tag compare than barcode make the system is more applicable to used in food traceability. In this case one of food product take into example in supplying which is banana that the process started from farmer until reach to retail house are monitored and recorded by the system. End process of this system is to give services to the consumer of customer based on EPCIS database collected in all the way of process. DOI: http://dx.doi.org/10.11591/telkomnika.v13i1.6919